The Impact of Digital Technology Transformation on Lecturer Performance in Higher Education: An Innovation Diffusion Perspective - Abdul Hamid; Tjutju Yuniarsih; Disman Disman; Budi Santoso (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the impact of digital technology on lecturers’ performance in higher education institutions. The analysis focuses on five key indicators: learning enhancement, teaching effectiveness, academic leadership, infrastructure readiness, and the availability of syllabi and lesson plans. Methodology: A mixed-methods approach was adopted, involving both quantitative and qualitative data collection. Questionnaires were distributed to 64 lecturers, and semi-structured interviews were conducted with selected participants. The instruments assessed lecturers’ attitudes, behaviors, and the extent of digital technology adoption across teaching, research, and community service activities. A Likert scale was used to measure the level of digital technology acceptance. Main Findings: The findings show that although many lecturers are still in the process of understanding and adapting to digital transformation, the use of digital technology has significantly improved their effectiveness and efficiency. It has also increased learning flexibility and student engagement through more interactive and accessible educational environments. Key supporting factors identified include institutional infrastructure, academic leadership, and supportive policies. Novelty/Originality of this study: This study contributes to the growing body of knowledge by exploring the multifaceted influence of digital technology on lecturers' performance. It highlights the critical role of institutional support in facilitating sustainable digital integration in higher education, particularly in the Indonesian context.